KAJIAN NILAI-NILAI FILOSOFIS KESENIAN WAYANG KULIT DALAM KEHIDUPAN MASYARAKAT JAWA - Ronaldo, Paskalis (Universitas Hasanuddin, 2023)
One of the popular and growing cultures in Indonesia is wayang. Wayang is closely related to the lives of the Javanese people because the story of wayang has developed and grown in Java. This is one of the characteristics of wayang that is never separated from the daily lives of Javanese people. Seeing this phenomenon, the author tries to review the philosophical values that exist in wayang in relation to the lives of the Javanese people. The method used to review these philosophical values is a literature study method that utilizes several sources of previous books and articles as references. In this paper, the author finds that every symbol used in wayang performances has a very deep philosophical value and meaning for the lives of the Javanese people. The philosophical values contained in wayang include ethics, culture, mysticism, a reflection of identity, human character, religiosity, nationality, and life guidelines.